The Evolution of the Scientific and Technological Capabilities of Industrial Enterprises Management - Vitaliy I. ZAKHARCHENKO; Tetiana V. AVERIKHINA; Oksana M. KRAVCHENKO; Inna D. GRECHKOSIY; Alona V. PISKUN; Krystyna I. TARASOVA (Communications of International Proceedings, 2024)
An analysis of ways to minimize costs and evaluation of products based on value added. It identifies actions to reduce costs based on clarifying the relationship between technology development and productivity with the involvement of the productive function. The regularities of the development of technological processes and the ways of the technologization of managing the effective development of an industrial enterprise are highlighted. Motivation of the research was to find out options for the appropriate modernization of production that can offer the greatest synergistic effect under the existing restrictions on the limits of scientific and technological development; social and psychological conditions for staff for creative work.
Keywords: Industrial Enterprise; Technology; Productivity; Expenses.